2015
DOI: 10.1093/femsle/fnv094
|View full text |Cite
|
Sign up to set email alerts
|

GH11 xylanase from Emericella nidulans with low sensitivity to inhibition by ethanol and lignocellulose-derived phenolic compounds

Abstract: An endo-β-1,4-xylanase (X22) was purified from crude extract of Emericella nidulans when cultivated on submerged fermentation using sugarcane bagasse as the carbon source. The purified protein was identified by mass spectrometry and was most active at pH and temperature intervals of 5.0-6.5 and 50-60°C, respectively. The enzyme showed half-lives of 40, 10 and 7 min at 28, 50 and 55°C, respectively, and pH 5.0. Apparent Km and Vmax values on soluble oat spelt xylan were 3.39 mg/mL and 230.8 IU/mg, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
2
2
1
Order By: Relevance
“…Phenolic compounds frequently inhibit a variety of cellulolytic enzymes, such as xylanases, through enzyme conformational changes with or without involvement of the substrate-binding site 42 . In contrast, however, a number of studies have also shown that phenolic compounds, such as FA, do not inhibit the activity of xylanases from Emericella nidulands 34 , Aspergillus terreus 40 , and may even increase the enzyme activity of xylanase 33 , as described in the present study for HXYN2.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Phenolic compounds frequently inhibit a variety of cellulolytic enzymes, such as xylanases, through enzyme conformational changes with or without involvement of the substrate-binding site 42 . In contrast, however, a number of studies have also shown that phenolic compounds, such as FA, do not inhibit the activity of xylanases from Emericella nidulands 34 , Aspergillus terreus 40 , and may even increase the enzyme activity of xylanase 33 , as described in the present study for HXYN2.…”
Section: Discussioncontrasting
confidence: 82%
“…The maximum activity of HXYN2 occurring at pH 6.0 is similar to that obtained for GH11 xylanases from Aspergillus tamarii 33 and Emericella nidulans 34 , where pH optimal values were 5.5 and 6.0, respectively. Previous reports show that the pH optimum of GH11 xylanases depends on the amino acid in proximity to the Glu catalytic acid–base residue 11 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…2). Similar to our work, Silva and co-workers reported differences in MS/MS fragmentation of their Emericella nidulans xylanase compared to that reported for other Emericella nidulans isolates-this was thought to be as a result of different isoforms of the enzyme from this fungal species, as the enzyme was produced from the same fungus, but grown under different conditions to those reported previously [14]. As a result, there were differences in PTMs and/or amino acid sequences of these isoforms.…”
supporting
confidence: 88%
“…Thermotolerance of the fermenting microorganism is a trait commonly searched for as previously described. New xylanases obtained from Emerciella nidulans [151] or marine bacteria Acinetobacter johnsonii [152] are being developed that not only show lower inhibition to ethanol, but a higher activity in its presence. Recent studies suggest that using H 2 O 2 as an oxidizing agent instead of oxygen in anaerobic SSF processes could work as a solution for LPMO competition with microorganisms, as long as the peroxide concentration is low enough so that the microorganism does not suffer inhibition [153].…”
Section: Improving Microbial Performance For Ethanol Productionmentioning
confidence: 99%